The distribution and accumulation of phthalates in the organs and tissues of chicks after the administration of feedstuffs with different phthalate concentrations - A. Jarosova; J. Harazim; P. Suchy; L. Kratka; V. Stancova (Veterinární Medicína, 2009)
For the monitoring of distribution and accumulation of phthalic acid esters (PAE) in animal tissues, samples of muscle, mesenteric fat (fat), skin and liver from broiler chicks ROSS 308 were used. The chicks were divided into four groups (50 chicks each). All the chicks were given commercial diets (complete feed, KKS) for broiler chicks (starter - BR1; grower - BR2 and finisher - BR3). The experimental diets were supplemented with vegetable oil (RV) with low (group N) or high (group V) phthalate contents, or animal fat with a high phthalate content (group Z). Neither the control diets (K), nor the grower (BR1) diets contained vegetable oils or animal fat. The N chicks were given the grower (BR2) and finisher (BR3) diets supplemented with 5% and 3% vegetable oil, respectively. The V chicks were given BR2 and BR3 diets with 5% and 3% vegetable oil, respectively. The Z chicks were given BR2 and BR3 diets with 5% and 3% animal fat, respectively. The chicks were fattened till 42 days of age. Dibutyl phthalate (DBP) and di-(2-ethylhexyl) phthalate (DEHP) were found in the tissues of chicks in all the experimental groups. The DBP content in the muscle ranged from 0.03 to 0.55 mg/kg, in the adipose tissue from < 0.20 to 2.56 mg/kg, in the skin from < 0.20 to 1.49 mg/kg, and in the liver from 0.03 to 0.13 mg/kg. The content of DEHP in the muscle ranged from 0.03 to 1.15 mg/kg, in the adipose tissue from 0.25 to 9.85 mg/kg, in the skin from < 0.20 to 4.68 mg/kg, and in the liver from 0.16 to 0.24 mg/kg. The highest concentrations of DBP of 1.28 ± 1.00 mg/kg of fresh sample (an average value from eight chicks) was determined in the adipose tissue of V chicks. The highest concentration of DEHP of 3.27 ± 2.87 mg/kg of fresh sample (mean of eight chicks) was also determined in the V group. The accumulation of DEHP was 3.2; 2.6 and 2.9 times higher than that of DBP in the muscle, adipose tissue and skin, respectively. The V and Z chicks showed higher phthalate contents (the sum of DBP and DEHP) in the adipose tissue, skin and liver than the K and N chicks.